(NaWTOMATIZIROWANNAQ LEKSIKOGRAFI^ESKAQ SISTEMA unileks (B:s (NsLOWARNO(B-(NORIENTIROWANNAQ PODSISTEMA (B/s - (NkOLODQVNAQ(B, (Nl@DMILA iWANOWNAs; (NpAWLOWI^(B, (Nn(B.(Nw(B.s ((NmOSKWA (B:s (Nmgu(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 107-112s
(Nmgu IM(B. (Nm(B. (Nw(B. (NlOMONOSOWA(B, (Nn(B.-(NI(B. (Nwcs
Keywords: (NaWTOMATIZACIQs; (NsOSTAWLENIEaWTOMATIZACIQs